Urdū adab aur Bangālī kalcar - Bhaṭṭācāryah, Shāntī Ranjan, 1930- (Magẖribī Bangāl Urdū Akāḍmī, 1982)
Articles on Urdu language and writers, and influence of Bengali culture on Urdu writing in Bengal.